(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
Mathematical models play important role in understanding the population dynamics of HIV/AIDS. In this study, a mathematical model is formulated for a community which has the structure of two classes with different levels of sexual activity one is high activity group that include commercial sex workers and their male customers; and the other is low activity group. These two groups are further divided into two sub-groups as HIV infected and unaware, and HIV infected and aware after screening. It is assumed that people in low activity group when become aware, do not spread infection any more by means of either not participating in sexual activity at all or by taking some preventive measures. The model is analysed using stability theory of differential equations, numerical simulation and sensitivity analysis.